A model for developing dependable systems using a component‐based software development approach (MDDS‐CBSD). Issue 1 (30th December 2022) - Kahtan, Hasan; Abdulhak, Mansoor; Al‐Ahmad, Ahmad Salah; Alzoubi, Yehia Ibrahim
Abstract: Component‐based software development (CBSD) is an emerging technology that integrates existing software components to swiftly develop and deploy big and complex software systems with little engineering effort, money, and time. CBSD, on the other hand, has difficulties with security trust, particularly dependability. When a system provides the desired outcomes while causing no harm to the environment, it is said to be dependable. Dependability encompasses several attributes, including availability, confidentiality, integrity, reliability, safety, and maintainability. Developing dependable component software is achieved by embedding dependability attributes in CBSD. Thus, the CBSD model must address the dependability attributes. Hence, the objectives of this work are: (1) to propose a model for developing a dependable system using component‐based software development approach (hereafter the model is referred to as MDDS‐CBSD), which aims to mitigate software component vulnerabilities, and (2) to assess the proposed model. The best‐practice method was used to frame the CBSD architecture phases and processes, as well as embed the six dependability attributes. The MDDS‐CBSD architecture was evaluated using expert opinion. The MDDS‐CBSD was also used to develop an information and communications technology (ICT) portal using an empirical study method. Vulnerability Assessment Tools were used to assess the developed ICT portal's dependability. The MDDS‐CBSD may be used to create web application systems and to protect them from attacks. Model developers may use CBSD to describe and assess dependability attributes at any point during the model development process. The reliability of this model can also let companies utilise CBSD with confidence. Abstract : This research proposes a model for developing a dependable system that mitigates software component vulnerabilities and assesses the proposed model.